Analisis Responsivitas Bursa Syariah oleh Variable Makroekonomi - Pratama, Yoghi Citra (Al-Iqtishad: Journal of Islamic Economics, 2012)
The objective of this study is to analyze the stock response because of M2, exchange rate (rupiah to US dollar), and rate of SBI. The data used in this study is monthly time series data from January 2006 until May 2012. Those variables are JII, M2, exchange rate rupiah to US dollar, and rate of SBI. Research method used in this study is Vector Error Correction Model (VECM). The cointegration test indicates that among research variables there is long term equilibrium and simultaneous relationship. The empirical result of impulse response show that the effect of SBI rate and M2 are negative and the effect of exchange rat is positive. The result on variance decomposition test, show that the most effect of JII shock is influenced by JII itself.DOI: 10.15408/aiq.v4i2.2100